2016
DOI: 10.1186/s12913-016-1914-4
|View full text |Cite
|
Sign up to set email alerts
|

Which aspects of health care are most valued by people living with HIV in high-income countries? A systematic review

Abstract: BackgroundIncreasing numbers of people with HIV are living into older age and experiencing comorbidities. The development of new models of care to meet the needs of this population is now a priority. It is important that the views and preferences of patients inform the development of services in order to maintain high levels of patient satisfaction and engagement. The aim of this systematic review was to determine which aspects of healthcare are particularly valued by people living with HIV.MethodsWe searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
4
19
0
2
Order By: Relevance
“…6,17 Without other LTCs, PLHIV may have little or no contact with a GP, sometimes causing apprehension. The present findings are consistent with a systematic review of aspects of health care most valued by PLHIV in high-income countries, 18 which could be summarised to three main areas: a good, supportive practitioner-patient relationship involving patients in care decisions; access to specialist high quality HIV knowledge and support; and well-functioning care structures that provide effective, accessible continuity of care and services for all.…”
Section: Comparison With Existing Literaturesupporting
confidence: 90%
“…6,17 Without other LTCs, PLHIV may have little or no contact with a GP, sometimes causing apprehension. The present findings are consistent with a systematic review of aspects of health care most valued by PLHIV in high-income countries, 18 which could be summarised to three main areas: a good, supportive practitioner-patient relationship involving patients in care decisions; access to specialist high quality HIV knowledge and support; and well-functioning care structures that provide effective, accessible continuity of care and services for all.…”
Section: Comparison With Existing Literaturesupporting
confidence: 90%
“…The attributes and levels were derived from a systematic literature review 13 and a qualitative study. The latter included people who were at least 16 years age and registered for care with an National Health Service (NHS) HIV clinic.…”
Section: Methodsmentioning
confidence: 99%
“…The attributes and levels were derived from a systematic literature review 13 and a qualitative study.…”
Section: Choice Of Attributes and Levelsmentioning
confidence: 99%
“…However, the review revealed a limited amount of research into patients' preferences for delivery of healthcare. 16 Recent fieldwork reported by the King's Fund has highlighted that although in general there is strong commitment to involving people in HIV services locally, almost all of the examples given were about how individual services operated, rather than how the various services combined to shape people's overall experience of living with HIV. 17 Therefore, aims of this study were to explore PLWHIV preferences for healthcare services outside of their HIV specialist services and to determine which aspects of care are valued.…”
Section: Introductionmentioning
confidence: 99%